Strategi Pemenangan Partai Kebangkitan Bangsa dalam Pemilihan Legislatif di Kota Tanjungpinang Tahun 2024 - Said Ridho Rizky Ramadhani; Nazaki Nazaki; Eki Darmawan (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The democratic system implemented in Indonesia is realized through general elections, which are held every five years as a manifestation of people’s sovereignty. Elections provide an arena for political contestation where political parties compete to gain votes and legislative seats, including the National Awakening Party (Partai Kebangkitan Bangsa/PKB). In the 2019 general election, PKB in Tanjungpinang City obtained 5,188 votes or 4.67%, securing two parliamentary seats. By contrast, in the 2024 general election, its vote share increased significantly to 9,765 votes or 7.94%, allowing the party to gain three seats. This increase indicates that the political strategies applied by PKB in Tanjungpinang had a substantial impact and are worth analyzing, as they succeeded in attracting voter support and expanding parliamentary representation. The purpose of this study is to identify and analyze the strategies used by the National Awakening Party in the 2024–2029 Tanjungpinang City Legislative Election. This research also explores strategic approaches not only at the party level but also by individual legislative candidates, who applied their own methods to secure voter trust. The study adopts Peter Schroder’s (2010) theoretical framework on political strategy, which includes situation analysis, strategy control, strategy formulation, strategy implementation, and strategy evaluation. This framework is employed to examine how PKB designed, executed, and assessed its strategic efforts during the electoral process. The findings demonstrate that PKB’s success was not merely due to party-level strategies but also the result of synergy between collective organizational moves and personalized campaign tactics by candidates. These strategies involved effective grassroots engagement, optimized use of political networks, and adaptation to the socio-political context of Tanjungpinang. The implications of this research suggest that comprehensive and adaptive political strategies are essential for increasing electoral gains, and that combining party-driven initiatives with candidate-level innovations can enhance both vote acquisition and seat attainment in legislative elections.